Leading the Way in Dementia Care: Embracing the Whole Person - Hickey, Ellen M.; Douglas, Natalie F.; Hopper, Tammy; Bourgeois, Michelle (Seminars in Speech and Language, 2024)
Audrey Holland was a leading innovator and speech-language pathologist (SLP) in adult neurological communication disabilities for over five decades. She was a pioneer in the involvement of SLPs with people with dementia, inspiring both knowledge development and clinical practice regarding language, functional communication, and quality of life in persons living with dementia. Dr. Holland was also an extraordinary mentor who has impacted many generations of researchers and clinicians. Here, four researchers in the area of dementia and communication discuss the lessons they learned from Dr. Holland that fundamentally shaped their careers and the field of dementia and speech-language pathology. Lessons learned include the following: (1) do not be afraid to stand out when you have a novel idea that will help people; (2) look for strengths to support functional communication; (3) use communication strategies to support identity, quality of life, and self-determination in adults with acquired communication disabilities, including those with dementia; (4) shift from pathologizing to coaching; and (5) challenge the status quo. This article concludes by discussing Dr. Holland's lasting legacy.
Keywords: person-centered care; functional communication; supported communication; communication strategies; DementiaBank